2018
DOI: 10.1126/science.aat4311
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-specific signatures in the chromosomal connectome associated with schizophrenia risk

Abstract: To explore the developmental reorganization of the three-dimensional genome of the brain in the context of neuropsychiatric disease, we monitored chromosomal conformations in differentiating neural progenitor cells. Neuronal and glial differentiation was associated with widespread developmental remodeling of the chromosomal contact map and included interactions anchored in common variant sequences that confer heritable risk for schizophrenia. We describe cell type–specific chromosomal connectomes composed of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
196
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(219 citation statements)
references
References 67 publications
16
196
0
Order By: Relevance
“…1A-C). These numbers are in line with the low number of reported ct-links experimentally observed for NPC, neurons, and K562 cells [15,16], and indicates that cell-type specific EP links constitute only a small portion of the EP links that are active in any particular cell type. CT-FOCS predicted EP links are on average shared across 3, 1.65, and 2.5 cell types in ENCODE, Roadmap, and FANTOM5 datasets ( Supplementary Fig.…”
Section: Figure 1 Outline Of the Ct-focs Algorithmsupporting
confidence: 79%
See 1 more Smart Citation
“…1A-C). These numbers are in line with the low number of reported ct-links experimentally observed for NPC, neurons, and K562 cells [15,16], and indicates that cell-type specific EP links constitute only a small portion of the EP links that are active in any particular cell type. CT-FOCS predicted EP links are on average shared across 3, 1.65, and 2.5 cell types in ENCODE, Roadmap, and FANTOM5 datasets ( Supplementary Fig.…”
Section: Figure 1 Outline Of the Ct-focs Algorithmsupporting
confidence: 79%
“…Third, the average number of CT-links per cell type was 167 in ENCDOE, 234 in Roadmap, and 414 in FANTOM5, respectively ( Table 1). While these numbers are very low, considering that ENCODE reported a total of ~3M regulatory elements [19], they are in line with the small number of cell type-specific EP links reported previously for NPC, neuron, and K562 cells [15,16]. Fourth, each promoter was linked to ~2 enhancers on average (and a maximum of 9) in each cell type.…”
Section: Columnsupporting
confidence: 79%
“…Cell type-specific promoter interactome maps thus provide insights into the epigenomic regulation of these cell types by linking putative enhancers and disease variants to target genes. A recent analysis of Hi-C chromatin loops using in vitro iPSC-derived neural progenitor cells, neurons and astrocytes identified dynamic chromatin reorganization during development and was used to generate an extended network of schizophrenia risk genes (82). Our approach of using proximity ligation coupled to an enrichment for promoter regions provided an 8.6-fold expansion in the number of detected neuronal chromatin loops.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes (321) were found to be potential targets for the regulators and have roles in various neurological functions such as synaptic activity and ion channel regulation. They also concluded that schizophrenia was primarily a neuronal disorder rather than glial [8]. …”
Section: Complicated Genetic Linksmentioning
confidence: 99%